Influence of Organizational Culture on Organizational Effectiveness in Higher Educational Institutions : Ownership as a Moderator - Subha, K.; Ramnath Babu, C. N. S. (Prabandhan: Indian Journal of Management, 2024)
Purpose : An organization’s effectiveness is significantly impacted by its organizational culture. This empirical study aimed to comprehend how private and government teaching professionals perceived the prevailing culture in their institutions and its influence on organizational effectiveness. It also assessed the moderating effect of ownership types on an institution’s effectiveness operating in Tamil Nadu, India. Design/Methodology/Approach : Competing Values Framework was adopted to determine the organizational culture. A pilot study was conducted to validate the survey instrument developed using Cameron’s Organizational Culture Assessment Instrument. This descriptive and cross-sectional study used the purposive sampling method to collect data. The questionnaire was sent to 956 email addresses, and the participants represented 82 colleges. Findings : The analysis revealed significant differences in the perception of clan and market culture between professionals working in private and government colleges. The ownership type of the educational institution negatively moderated the relationship between perceived market culture and organizational effectiveness. Practical Implications : The findings demonstrated the importance of effective strategy and culture in determining an institutional mission that can be successfully carried out. Regardless of its ownership type, higher educational institutions should focus on building and fostering the critical dimensional characteristics of cultures, with a particular emphasis on adhocracy to advocate its effectiveness. Originality/Value : The study may be extended in diverse educational contexts to gain comprehensive knowledge about the relationship between organizational culture and effectiveness.